An Analysis of the Law Relating to the Prohibition of Torture in India (Journal of Advances and Scholarly Researches in Allied Education, 2023)
In the present review paper, the legal framework in India that pertains to the prohibition of torture is investigated. Particular attention is paid to international agreements, contextual circumstances, statutory provisions, and the viewpoint of the court. India's ratification of the United Nations Convention against Torture and Other Cruel, Inhuman, or Degrading Treatment or Punishment (UNCAT) is investigated in this study. Additionally, other pertinent international instruments, such as the European Convention on Human Rights (ECHR) and the International Covenant on Civil and Political Rights (ICCPR), are also taken into consideration. International instruments that are pertinent to the research include both of these conventions, which are instances of international instruments. It examines the evolution of torture throughout time, the expansion of human rights organizations, and the establishment and ratification of the United Nations Convention on the Rights of the Child. The paper discusses constitutional provisions and criminal laws in India related to torture and highlights landmark judicial decisions that uphold the prohibition of torture. Challenges in implementing anti-torture laws and the judiciary's role in curbing torture are also discussed. The summary emphasizes the need for specific anti-torture legislation, sensitization programs, and public awareness campaigns to combat torture effectively.